(untitled) (European Journal of Formal Sciences and Engineering, 2021)
This study aims to indicate the role of the communication process and new technologies in the crisis management, by showing deferent concepts related to the crisis management, its phases, how can we manage crisis using communication, and how can we use technology to manage crisis. The main idea of this study is that stakeholders (internal or external) are very important to overcome on a crisis, and every organization must identify the full range of its stakeholders, so it can receive their help when it is necessary.